ANALISIS PENGGUNAAN MEDIA POP UP BOOK DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Paulina, Windi; Muslihah, Neni Nadiroti; Nuriyanti, Risma; Mutaqin, Ejen Jenal (caXra: Jurnal Pendidikan Sekolah Dasar, 2021)
This study aims to describe the use of popup book media in mathematics learning. The participants were low-class students at Kp. Babakan Bungbulang which was held in a learning family. Desscriptive qualitative is used as a research method by collecting data using observations, questionnaires and wawancra. Triangulation of data used is 1) to see the analysis of media usage to learners whether it is classified as a good media used it is based on the results of interview tests and questionnaires, 2) The results showed that the learners greatly appreciated the popup book learning media applied in mathematics learning that has been carried out in the second observation. This shows that the results of this popup book media analysis research can help students in learning with increased learning ability, especially in mathematics learning